The Effect of Sodium Hyaluronate plus Sodium Chondroitin Sulfate Solution on Peritendinous Adhesion and Tendon Healing: An Experimental Study - Tosun, Haci Bayram; Gumustas, Seyit Ali; Kom, Mustafa; Uludag, Abuzer; Serbest, Sancar; Eroksuz, Yesari (Galenos Publ House, 2016)
Background: Adhesion formation following tendon injury is a serious clinical problem. Aims: In this experimental study, the effects of the combination of sodium hyaluronate (HA) and chondroitin sulfate (CS) on peritendinous adhesion and tendon healing were evaluated. Study Design: Animal experimentation. Methods: Twenty-one mature Sprague Dawley male rats were randomly divided into three equal groups. The rats Achilles tendons were cut and repaired with a modified Kessler technique. About 0.25 and 0.50 mL of the HA and CS (HA+CS) combination were injected subcutaneously into the repair site of the rats in groups 1 and 2, respectively, on days 0, 3, 7, and 10. The subjects in group 3 were used as the control group. At 6 weeks, all rats were euthanized. The tenotomy site was examined macroscopically in all animal subjects. Four samples were assigned to the histopathological examination group, and the others were assigned to the biomechanical assessment group. Results: Inflammation and adhesion in both treatment groups were observed at a lower rate than in the control group. The collagen filaments in both treatment groups were regular and the number was low when compared to the control group. However, there was no statistically significant difference between group 1 and the control group. The quantity, quality, and grade of the adhesions were statistically significantly lower in group 2 when compared with the other groups. The mean maximum stress strength in group 2 was statistically significantly higher than that in group 1 and the control group. Conclusion: Local administration of the HA+CS combination solution is a valid tool for preventing peritendinous adhesion after extrasynovial tendon repair such as Achilles tendon, and is a treatment option in such cases.
Keywords: Chondroitin sulfate; hyaluronate; peritendinous adhesion; tendon healing